2012
DOI: 10.1007/s10006-012-0323-z
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial trauma and seat belt: a 10-year retrospective study

Abstract: Classically, it is known front seat belt use was positively correlated with back seat belt use, healthy diet, dental and general health, regular walking, adequate sleep and no smoking. Accidents involving cars occurred more frequently in age group 18-30 years, suffering more general traumas and representing the nonusers group that wore fewer seat belts, caused, perhaps, by bigger access of the youth to cars, driving in high speed and to an inefficient fiscalization of the traffic laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
3
12
0
1
Order By: Relevance
“…Confirming the results of this study, other authors (18) (18). Similarly, Mendes et al (6) in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Confirming the results of this study, other authors (18) (18). Similarly, Mendes et al (6) in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 91%
“…Confirming the results of this study, other authors investigated 1531 records from traffic accidents in 2007 and 2009 in the North District of Rio de Janeiro and observed a prevalence of 40.2% due to motorcycle accidents in 2007 and 42.3% in 2009, while car accidents were 22.1% and 23.4% in 2007 and 2009, respectively . Similarly, Mendes et al in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Epidemiological studies in different parts of the world indicate that RTAs are the main etiological factors of facial trauma and the specific interest has been directed towards the incidence and prevention of these lesions . Maxillofacial injuries usually affect the middle third of the facial skeleton and mandible, especially soft tissues.…”
Section: Discussionmentioning
confidence: 99%